Gender Differences in Biochemical ExaminationAmong Paint Industry Workers - Purwati; Indah Tri Susilowati; Noviana Dewi; Chusnul Chotimah; Ratna Setyaningrum; Tri Harningsih; Dewi Saroh (Jurnal Kesehatan Masyarakat, 2026)
The production of paint involves the use of volatile organic compounds (VOCs) and heavy metals, which can impact health. Gender differences play a significant role in toxicokinetics and toxicodynamics. Variations in sex hormones, xenobiotic-metabolizing enzymes, and distribution volumes influence the body's response to toxins. This study aims to investigate biochemical parameters—including ALP, AST, ALT, Gamma-GT, total cholesterol, creatinine, cholinesterase, total bilirubin, fasting glucose, N Urea, eLFG, and uric acid—in paint industry workers, stratified by gender. An analytical observational study with a cross-sectional design was conducted on 89 workers engaged in production, research and development, and logistics within a paint manufacturing facility. Demographic data were obtained via questionnaires, and laboratory test results were analyzed. Statistical evaluation was performed using the chi-square test to determine the association between gender and biochemical abnormalities, with an odds ratio (OR), 95% confidence interval (CI), and significance level set at p<0.05. The assessment of paint exposure among workers, based on biochemical test results stratified by gender, demonstrated that gender significantly influences these parameters (p<0.05). The findings of alkaline phosphatase (ALP) (OR: 7.500, 95% CI: 1.146–49.100), total cholesterol (OR: 3.841, 95% CI: 1.142–12.916), and creatinine (OR: 30.179, 95% CI: 7.706–118.193) suggest that exposure to paint substances impacts liver function (as indicated by ALP), total cholesterol, and renal function (creatinine). These outcomes may be attributed to physiological, hormonal, enzymatic, and genetic differences between male and female individuals in their toxicological responses, as supported by biochemical examination results.